The business school in the twenty-first century emergent challenges and new business models - Thomas, Howard 1943- (Cambridge University Press, 2013)
Questions about the status, identity and legitimacy of business schools in the modern university system continue to stimulate debate amongst deans, educational policy makers and commentators. In this book, three world experts share their critical insights on management education and new business school models in the USA, Europe and Asia, on designing the business school of the future, and how to make it work. They look at how the business school is changing and focus in particular on emergent global challenges and innovations in curricula, professional roles, pedagogy, uses of technology and organisational delineations. Set within the context of a wider discussion about management as a profession, the authors provide a systematic, historical perspective, analysing major trends in business school models, and reviewing a wealth of current literature, to provide an informed and unique perspective that is firmly grounded in practical and experimental analysis
Title from publisher's bibliographic system (viewed on 05 Oct 2015)
Keywords: Business schools; Business education; Management / Study and teaching; Managementschule; Hochschuldidaktik; Ausbildungsziel; Betriebswirtschaftliches Studium